Cfd Simulation Of Micro Hydro-Kinetic Turbine - Idrus, Muhamad Affiq Iruan (Universiti Sains Malaysia, 2021)
Hydrokinetic energy refers to the energy produced by ocean currents, tidal currents, rivers and artificial water channels from flowing water. Several technologies, such as horizontal axis hydrokinetic turbines, have been developed to extract this energy. Savonius turbine is a cost-effective electric generation used in the low-velocity region. The conventional Savonius wind turbine with semicircular blades has a relatively low power coefficient than other wind turbines that are available out there. Since the turbine itself is not fully explored by researchers, several improvements can be made for this turbine. Some improvements had been made for the turbine to increase performance in terms of coefficient of power and torque coefficient for the best possible result. The main objective of this project is to improve the turbine coefficient of the turbine's performance that will be used in water instead of wind. The Savonius model used in this project is from (Golecha et al., 2011) optimization design since it is already achieving the peak of the power coefficient of the Savonius can be achieved. In this project, the Savonius turbine blade will be used as an optimization to compare with (Golecha et al., 2011) design. This project will also be studied the maximum power coefficient that can be achieved by changing the rotor center of the novel Savonius turbine. The design will be tested through simulation using Ansys pressure-based solver, which is to study the interaction between the structural model and the fluids passing through it. The coefficient of power and coefficient of torque for the different configurations of the blade are studied. The modified Savonius turbine of Design 4 has the highest coefficient of power of all of the designs, 8.53%, at a TSR of 0.68, which is the maximum Cp possible in this experiment. At a tip speed ratio of 0.68, a maximum coefficient of power of 0.1644 is observed. When the tip ratio is at its maximum power coefficient, the highest coefficient of torque is 0.2430. As for Design 1, Design 2, Design 3, Design 5, and Design 6, the increment for the coefficient of the power is 4.33%, 7.65%, 5.20%, 5.71%, 6.34%, respectively. The study of the fluid flow across the most maximum coefficient of power for the optimization Savonius turbine was also achieved in this project.